2002
DOI: 10.1177/153331750201700604
|View full text |Cite
|
Sign up to set email alerts
|

Professional caregivers for patients with dementia: Predictors of job and career commitment

Abstract: The purpose of this study is to identify what factors predict job and career commitment among professional caregivers working with patients with dementia. A secondary analysis was completed using data collected from 77 professional caregivers working in residential dementia special care programs. The findings suggest that professional caregivers' commitment to their jobs and careers is most closely related to their level of involvement in the interpersonal aspects of the work, the degree to which they feel per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…Trust in God has been discussed as the most common coping mechanism when facing stressful situations (23). Because of their problems, the staff should be patient and recognize the patients' physical and cognitive changes which leads to inability in their daily activities (24). The study showed that empathy with patients mostly depended on the characteristics of the health professional (25).…”
Section: Discussionmentioning
confidence: 99%
“…Trust in God has been discussed as the most common coping mechanism when facing stressful situations (23). Because of their problems, the staff should be patient and recognize the patients' physical and cognitive changes which leads to inability in their daily activities (24). The study showed that empathy with patients mostly depended on the characteristics of the health professional (25).…”
Section: Discussionmentioning
confidence: 99%
“…Job‐related well‐being has been identified as a key area of concern for attracting and retaining staff caring for people with dementia (Drebing et al . , Vernooij‐Dassen et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…While much research on formal caregiving has focused on extrinsic factors, some has pointed to the lack of opportunities for agency workers to develop extended caregiving relationships with their clients (Barber & Iwai, 1996;, noting that heightened involvement with the interpersonal aspects of care and greater sense of personal growth have been associated with high job satisfaction and commitment among paid caregivers (Drebing, McCarty, & Emerson Lombardo, 2002;Eustis & Fischer, 1991).…”
Section: Quality Of the Caregiver-care Recipient Relationshipmentioning
confidence: 99%